The New Migration in Europe
XVI, 264 p.
Keywords: Recent migration in Europe has a whole range of characteristics which are said to distinguish it from earlier migration, and the description 'new migration' is often used. Based on a wide range of empirical case studies of the new migration, this book asks three critical questions. To what extent is the description 'new' conceptually valid? How is the new migration defined and by whom? How is the new migration experienced by migrants themselves?